NATIONAL INDICATORS REFLECTING THE DEVELOPMENT OF THE DIGITAL ECONOMY AND THEIR ANALYSIS (International journal of artificial intelligence, 2026)
The rapid development of the digital economy has become one of the key drivers of sustainable economic growth, competitiveness, and innovation in modern societies. National digital economy indicators play a crucial role in assessing the level of digital transformation, identifying strengths and weaknesses, and shaping effective public policies. This article aims to analyze the main national indicators that reflect the development of the digital economy, including digital infrastructure, human capital, digital innovation, e-government services, and digital business activity. The study examines international approaches to measuring the digital economy, compares widely used global indices, and discusses their applicability at the national level. Special attention is paid to the analytical interpretation of these indicators and their role in strategic economic planning. The results of the analysis highlight the importance of a comprehensive and integrated indicator system for accurately assessing digital economic development and ensuring long-term national competitiveness.